Alternatives to surgery in children with mild OSA. Issue 3 (1st July 2021) - Gozal, David; Ismail, Mahmoud; Brockmann, Pablo E.
Abstract : Precision medicine requires coordinated and integrated evidence‐based combinatorial approaches so that diagnosis and treatment can be tailored to the individual patient. In this context, the treatment approach to mild obstructive sleep apnea (OSA) is fraught with substantial debate as to what is mild OSA, and as to what constitutes appropriate treatment. As such, it is necessary to first establish a proposed consensus of what criteria need to be employed to reach the diagnosis of mild OSA, and then examine the circumstances under which treatment is indicated, and if so, whether and when anti‐inflammatory therapy (AIT), rapid maxillary expansion (RME), and/or myofunctional therapy (MFT) may be indicated.